From nucleoporins to nuclear pore complexes - Doye, Valérie; Hurt, Ed (Current opinion in cell biology, 1997)
One of the largest supramolecular assemblies in the eukaryotic cell, the nuclear pore complex, is now being dissected into its numerous molecular constituents. The combined use of biochemistry and genetics in yeast has made this rapid development possible. Although less is known about vertebrate nucleoporins, the first clues are now emerging about their in vivo function also. Much remains to be learned about nuclear pore complex assembly and function, however.